Key Factors for University Business Incubator Implementation (UBI): Literature Review - Adriansyah, Ahmad; Rimadias, Santi (PT. Riset Press International, 2024)
Business and entrepreneurship are risky activities, especially for new business people. One of the ideal business incubators is the one created by the campus, which is referred to as the University Business Incubator (UBI). However, it is not easy to ensure that UBI successfully carries out its vision and mission, for that it is necessary to study the Key Success Factors (KPIs) of UBI's success. From the criteria set, 15 articles become the unit of analysis of this literature review research. The results of the review found 7 conclusions. First, there are 3 aspects in making UBI, namely organization, service, and measuring the success of UBI and tenants. Second, important organizational aspects are UBI management, capital support, technology, facilities, ideas, networks, strategies, as well as communication or promotion. Third, the aspect of services to be provided depends on the location of the country and the business character of the tenant. Fourth, the recommended physical services are office space and production space. Non-physical services recommended are training/ consulting/ assistance, capital support, technology, facilities and ideas, networks, strategies, and communication or promotion of tenant products. Fifth, the recommended training areas are business technical, marketing, finance and banking, export-import, law, human resources and product development. Sixth, the role of the academic community can be as experts, sources of business networks, and other support personnel. Seventh, UBI success measurement can be done using financial performance and can be combined with operational performance.